Implicações da capoeira na trajetória de adolescentes-jovens em Sobral-Ce - Oliveira, Gleicivânia Eleutério de (2024)
In the Brazilian educational scenario, Laws 10.639/03 and 11.645/08 determine the mandatory inclusion of the study of Afro-Brazilian and indigenous history and culture in schools, with capoeira standing out as an essential part of this curriculum. Understanding these cultures is fundamental to promoting the decolonization of psychological and educational spaces. Although educational institutions have advanced in terms of methodologies and practices, there are still gaps that can result in segregation and a feeling of not belonging on the part of some students. This research aims to analyze the implications of capoeira on the trajectory of young capoeiristas, investigating how this practice impacts their personal development and their permanence in the activities. The study is based on memories and field notes recorded by the first author, who acts as a reflective researcher, enriched by direct experience in the study environment. Using a qualitative approach, the research uses autobiographical narratives as a method of data collection. This work is composed of two studies that gathered testimonies from young people who participate in the Expressa Capoeira Project at the Lysia Pimentel School and the Feminino Mulheres de Luanda collective, both located in Sobral, Ceará. The first study addresses the historicity of capoeira, its developments, and the influence of musicality on the active participation of women in capoeira. The second study points out the changes in educational projects in the Brazilian context, contributions to an Afro- referenced curriculum, and the perceptions of young people about the implications of capoeira in their trajectories. The narratives show that capoeira goes beyond a simple physical practice, promoting the appreciation of Afro-Brazilian culture and contributing to the decolonization of the school environment, especially when included as part of the curriculum. In addition, capoeira strengthens protagonism, providing them with a space for inclusion and free expression. Musicality, a fundamental element of capoeira, is highlighted as a significant means of self-expression, both inside and outside the educational context represented by schools. However, participants also expressed the need for greater integration of African and Afro-Brazilian culture in these contexts, pointing out that there are still challenges to be overcome before studies on Ethnic-Racial Relations can be fully incorporated. The results of this research were presented at a technical event aimed at professionals who develop social projects in the region, with the aim of strengthening public policies aimed at children and adolescents. The initiative seeks to expand the reach of capoeira as an educational tool, promoting inclusion and strengthening the role of this practice in schools.